2018
DOI: 10.1177/1591019918785911
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical clipping and endovascular flow diversion of ruptured anterior circulation blood blister-like aneurysms

Abstract: Background Detection and treatment of blister-like intracranial aneurysms as a source of subarachnoid hemorrhage (SAH) can be challenging. In the past the results of both microsurgical and endovascular treatment were difficult. We present our experience with the treatment of blister-like aneurysms in the acute phase of SAH using microsurgical clipping, endovascular parent vessel occlusion or flow diversion. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The treatment options for BBAs are microsurgery, endovascular therapy (EVT), or a combination of two ( 4 ). Comparison of two treatment strategies showed that EVT for BBAs of the ICA is more effective and safe than surgical approaches ( 5 , 16 , 21 , 22 ). A systematic review by Rouchaud et al compared overall EVT techniques and reported that deconstructive techniques have a higher rate of immediate complete angiographic occlusion but a higher risk of ischemic complications when compared to reconstructive techniques ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment options for BBAs are microsurgery, endovascular therapy (EVT), or a combination of two ( 4 ). Comparison of two treatment strategies showed that EVT for BBAs of the ICA is more effective and safe than surgical approaches ( 5 , 16 , 21 , 22 ). A systematic review by Rouchaud et al compared overall EVT techniques and reported that deconstructive techniques have a higher rate of immediate complete angiographic occlusion but a higher risk of ischemic complications when compared to reconstructive techniques ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical sequelae of any complication were classified as "transient neurological deficit, " "permanent minor neurological deficit" (i.e., mRS 1 or 2), "permanent major neurological deficit" (i.e., mRS 3-5) or "death." (9).…”
Section: Data Collection and Follow-upmentioning
confidence: 99%
“…Technological improvements in intervention devices have led to improved safety and recovery rates associated with endovascular methods (5). A previous double-center study reported that the rates of complete occlusion and recovery in BBAs when using endovascular treatment were 72.9 and 64%, respectively (3,9,10). Owing to the lack of an ideal therapeutic strategy for BBAs, we reported the safety and efficacy of WCSs and double stent-assisted coils in the treatment of BBAs.…”
Section: Introductionmentioning
confidence: 98%
“…Blood blister-like aneurysm (BBA) is a special type of intracranial aneurysm with a relatively low morbidity and high mortality (1)(2)(3). Most BBAs are located in the anterior wall or the anterior medial wall of the non-branching sites of the supraclinoid segment of the internal carotid artery (ICA).…”
Section: Introductionmentioning
confidence: 99%